A Comparative Evaluation between New Ternary Zirconium Alloys as Alternative Metals for Orthopedic and Dental Prosthetic Devices. Issue 2 (February 2014) - Shyti, Genti; Rosalbino, Francesco; Macciò, Daniele; Scarabelli, Linda; Quarto, Rodolfo; Giannoni, Paolo
Purpose: We assessed in vitro the corrosion behavior and biocompatibility of four Zr-based alloys (Zr 97.5 Nb 1.5 VM 1.0 ; VM, valve metal: Ti, Mo, W, Ta; at%) to be used as implant materials, comparing the results with grade-2 titanium, a biocompatible metal standard. Methods: Corrosion resistance was investigated by open circuit potential and electrochemical impedance spectroscopy measurements as a function of exposure time to an artificial physiological environment (Ringer's solution). Human bone marrow stromal cells were used to evaluate biocompatibility of the alloys and their influence on growth kinetics and cell osteogenic differentiation through histochemical and gene expression analyses. Results: Open circuit potential values indicated that Zr-based alloys and grade-2 Ti undergo spontaneous passivation in the simulated aggressive environment. High impedance values for all samples demonstrated improved corrosion resistance of the oxide film, with the best protection characteristics displayed by Zr 97.5 Nb 1.5 Ta 1.0 . Cells seeded on all surfaces showed the same growth kinetics, although matrix mineralization and alkaline phosphatase activity were maximal on Zr 97.5 Nb 1.5 Mo 1.0 and Zr 97.5 Nb 1.5 Ta 1.0 . Markers of ongoing proliferation, however, such as podocalyxin and CD49f, were still overexpressed on Zr 97.5 Nb 1.5 Mo 1.0 even upon osteoinduction. No relevant effects were noted for the CD146-expressing population of bone progenitors. Nonetheless, the presence of a more differentiated cell population on Zr 97.5 Nb 1.5 Ta 1.0 samples was inferable by comparing mineralization data and transcript levels of osteogenic markers (osteocalcin, osteopontin, bone sialoprotein, and RUNX2). Conclusions: The combination of passivation, corrosion resistance and satisfactory biotolerance to bone progenitors make the Zr-based alloys promising implant materials. Among those we tested, Zr 97.5 Nb 1.5 Ta 1.0 seems to be the most appealing.